The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcb.27065
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: TPX2 gene silencing inhibits cell proliferation and promotes apoptosis through negative regulation of AKT signaling pathway in ovarian cancer

Abstract: Ovarian cancer (OC) is the leading cause of death from gynecological malignancy. Accumulated studies have revealed that targeting protein for Xklp2 (TPX2) was tightly associated with the development and progression of OC. The present study further determined a novel mechanism of TPX2 in OC via the AKT signaling pathway. The differentially expressed genes were screened in GEO database for gene expression microarray of OC. Bioinformatics was used to analyze the key differentially expressed genes in OC. We prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The development and progression of HCC are associated with multiple signaling pathways, such as the PI3K/AKT, MAPK/P38, JAK2/STAT3, TGF-β/Smad and NF-κB signaling pathways (22-26). Previous studies have found that TPX2 can regulate the proliferation and apoptosis of a number of different types of malignant tumors via the PI3K/AKT signaling pathway (13,16). In the present study, the potential effects of TPX2 silencing on the expression levels of PI3K/AKT signaling pathway-associated factors in Huh7 or Hep3B cells were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and progression of HCC are associated with multiple signaling pathways, such as the PI3K/AKT, MAPK/P38, JAK2/STAT3, TGF-β/Smad and NF-κB signaling pathways (22-26). Previous studies have found that TPX2 can regulate the proliferation and apoptosis of a number of different types of malignant tumors via the PI3K/AKT signaling pathway (13,16). In the present study, the potential effects of TPX2 silencing on the expression levels of PI3K/AKT signaling pathway-associated factors in Huh7 or Hep3B cells were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…However, upregulation of TPX2 can cause centrosome amplification and lead to DNA polyploidy (9). Previous studies have found that TPX2 is upregulated in a wide range of malignant tumors, including esophageal cancer (10), colon cancer (11,12), breast cancer (13), cervical cancer (14,15), ovarian cancer (16), bladder carcinoma (17) and medullary thyroid carcinoma (18). To the best of our knowledge, there are no studies on the association between TPX2 and the occurrence and development of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…1B) was significantly upregulated (Fig. 1C) in OC and was partly responsible for cancerous growth in OC (44,48,49). However, researchers are yet to study its effect on OC cells.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, TPX2 may provide insights into tumor cell proliferation. Evidence documented in the literature suggested that TPX2 was upregulated in such tumors as cervical cancer, lung cancer, pancreatic ductal adenocarcinomas, bladder cancer, OC and colon cancer (38)(39)(40)(41)(42)(43)(44). More importantly, a recent study revealed that miR-485-3p could suppress colorectal cancer by targeting TPX2 (45).…”
Section: Introductionmentioning
confidence: 99%
“…Role of TPX2, a microtubule associated protein, was also confirmed in HR in EAC cells. TPX2 has been shown to contribute to survival in ovarian 28 and endometrial 29 cancers. Cancer cells with increased genetic instability also show increased sensitivity to suppression of TPX2 30 .…”
Section: Discussionmentioning
confidence: 99%